National survey of catheter ablation for atrial fibrillation: The Japanese catheter ablation registry of atrial fibrillation (J‐CARAF). Issue 4 (17th July 2013) - Inoue, Koichi; Murakawa, Yuji; Nogami, Akihiko; Shoda, Morio; Naito, Shigeto; Kumagai, Koichiro; Miyauchi, Yasushi; Yamane, Teiichi; Morita, Norishige; Mitamura, Hideo; Okumura, Ken; ,
Abstract: To assess the current status of atrial fibrillation (AF) ablation in Japan, the Japanese Heart Rhythm Society (JHRS) instituted a national registry, the Japanese Catheter Ablation Registry of AF (J‐CARAF). Methods: Using an online questionnaire, the JHRS invited electrophysiology centers in Japan to voluntarily and retrospectively register data regarding the AF ablation procedures performed in September, 2011. Results: A total of 128 centers submitted data regarding AF ablation procedures in 932 patients (age 62.1±10.4 years; male 76.8%; paroxysmal AF 65.7%, CHADS2 score 1.0±1.0). The majority received oral anticoagulant therapy during and following the procedure (68.9% and 97.5%, respectively). Pulmonary vein isolation (PVI) was performed in 97.5% of the patients; ipsilateral encircling PVI was the preferred technique (79.7%). Three‐dimensional (3D) mapping systems and irrigated‐tip catheters were used in 94.8% and 87.7% of the procedures, respectively. Ablation methods other than PVI were performed in 78.8% of all the patients and 73.5% of the patients with paroxysmal AF. Acute complications were reported in 6.2% of the patients, but no early deaths were recorded. Conclusions: Ipsilateral encircling PVI, using 3D mapping and irrigated‐tip catheters, is the standard AF ablation method in Japan. However, adjunctive ablations were performed frequently, even in patients with paroxysmal AF.